The impact of deposition area and time on Touch DNA collected from fabric. (December 2022) - Alketbi, Salem K.; Goodwin, W.
Abstract: Touched items at crime scenes are frequently analysed to help link suspects to crimes, for example, Touch DNA is collected from victims' clothes in cases such as sexual assault, homicide, theft etc. Tape lifting is the preferred collection method of choice for trace DNA from clothes, fabric items and porous surfaces such as paper, therefore this study investigated the impact of deposition area and time on Touch DNA collected from fabric using minitapes. The amount of Touch DNA collected from the fabric was significantly affected by deposition area ( p  < 0.05), time ( p  < 0.05) and the interaction between the deposition area and time ( p  < 0.05), with the quantity of DNA collected decreasing over time. Also, the buttocks area of the trouser compared to the chest area is more prone to friction from an activity like repeatedly sitting on different surfaces which reduces the amount of Touch DNA available. In conclusion, it is more effective to collect trace DNA from victim clothes as soon as possible after the crime is committed.